RESPONSE OF THREE-WAY CROSS HYBRIDS AND TESTER OF CORN IN THE CENTRAL MEXICAN HIGHLAND - Torres Flores, José Luis; Morales Rosales, Edgar Jesús; González Huerta, Andrés; Laguna Cerda, Antonio; Córdova Orellana, Hugo (Revista Mexicana de Ciencias Agrícolas, 2018)
The identification of hybrids formed with three outstanding lines with germplasm from different research institutions could contribute to increase the heterosis in grain’s yield and the stability of maize planted in the High Valleys of Central Mexico. This work was conducted in 2009 in ten environments of this region with the aim to identifying outstanding genetic material. In an alpha lattice experimental design with two 8∗5 replicates per environment, we evaluated 40 genotypes of maize: early white trilinear 32 hybrids, four single crosses (testers) and four controls from CIMMYT. The most outstanding results indicated the following: a) the environments recorded with a higher production than 9.5 t ha-1 were Tlahuelilpan, Batán (+) and Batán (AC) but, Tlaxcoapan was the one with average stability and yield b) fifteen cob genotypes had statistically similar yields between 8.2 and 9.4 t ha-1, but the nones with the highest production were identified by the codes 21, 28, 27, 29 and 20 (CMS989001//Mexico gpo. 10; CMS 989003//Tuxpeño Cream 1; CMS 989003//SB1; CMS 989003//Mexico gpo. 10; CMS 989001//Tuxpeño Cream 1), with very acceptable arithmetic means in favorable environments and under conditions of low fertility and drought, but unstable, due that, out of these, only genotype 27 was the most stable over the ten contrasting environments. The best testers were identified by codes 35 and 36 [CMS 989 001 (P3) and CMS 989 003 (P4)], both with 9.3 t ha-1. The best trilinear hybrid control was identified with the key 39 and, the origin CMT 089,005, with 8.5 t ha-1. The best control and, the best testing had ear yields statistically identical as the 15 most outstanding hybrids. The subgroput of genotypes composed of the five trilinear hybrid and, the two testers, with the largest ear productions, are the most prominent genetic material for use in a new breeding program, and generate production technology or planting recommendation trade in this region of Mexico.
Keywords: Zea mays L.; ear cob’s production; High Valleys; hybrids of three lines; multivariate methods